Evaluación del manejo residuos sólidos bioinfecciosos y biocontaminados generados en las clínicas Santa Fe y San Lucas - Machuca Cabrera, Frank José (2014)
The present research aims to generate information regarding the study of bio-infectious solid waste and biocontaminated which are produced in facilities both public and prívate health, in that sense, what has been implemented in this thesis is conduct a situational analysis of the current generation of solid waste are generated in the San Fe Clinic and Clinic San Lucas Moyobamba, the same that are working according to their own perception as a company and according to resources available that the company goes in this direction is not fully complying with the stipulations of the Regulations of the General Law of Solid Waste and established the Ministry of Health through the Sector Executive Management Regulation and Enforcement of Health DIRES - San Martín; likewise the physical characterization of solid waste that are produced in these two establishments of Health, on the other hand al so was formulated and elaborated a preliminary proposal for a Management Plan for Solid Waste treatment and control mainly of activities performed collection storage, disposal bbioinfecciosos ty, biocontaminated and hazardous waste produced in the San Lucas and Clinics Clinics Santa Fe our Moyobamba. Finally we are pleased to provide this work to the authorities of our province Moyobamba, so they can make better decisions regarding the administration and management oftechnical-operational part oftheir waste are generating.